NEW DIMENSION OF INTRAMURAL SPORTS IN SCHOOL - Singrungruang, Pongkasem (Journal for Developing the Social and Community, 2021)
ABSTRACT Intramural Sports as part of physical education activity at school are held with the aim for students to use their potential to organize a sporting competition, in terms of management of personnel, financial and budget matters as well as venues, equipment and the whole process of organizing those events. Through such experience, students become aware of their roles, learn to work as a team, become good leaders and followers, willingly make sacrifice, and comply with competition rules. This helps participating students better understand the principle and philosophy of physical education, that is, learning to win, lose and forgive, including helping them develop from physical, mental, emotional, social and cognitive perspectives in order to become well- rounded human beings. New dimension of intramural sports in school was the process that was organized through principle of business management. That process has several components; planning organizational management, leadership and conducting. These components were integrated with the specific sports which were performed in school by teachers. The teachers have to justly perform the sport competition. In addition, these performances were effectively operated by teachers in order to meet highly goals. The sports in school are many types such as physical activities, Thai sports, international sports, recreational activities and physical fitness activities. These sports can enhance the students’ health and exercise attribute.